2022
DOI: 10.3390/en15197290
|View full text |Cite
|
Sign up to set email alerts
|

Planning, Operation, and Design of Market-Based Virtual Power Plant Considering Uncertainty

Abstract: The power systems of today seem inseparable from clean energy sources such as wind turbines (WTs) and photovoltaics (PVs). However, due to their uncertain nature, operational challenges are expected when WT and PV energy is added to the electricity network. It is necessary to introduce new technologies to compensate for the intermittent nature of renewable energy sources (RESs). Therefore, rationally implementing a demand response (DR) program with energy storage systems (ESSs) in a virtual power plant (VPP) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The authors found that the proposed model was useful for increasing profit while reducing emissions which benefits the environment. The authors of [20] recommended the implementation of a DR with ESSs in a VPP environment as a means to reduce the unpredictable behaviour or RESs and enhance the reliability of the power system. The proposed strategy attempted to optimize social wellbeing.…”
Section: Existing Literature and Research Gapmentioning
confidence: 99%
“…The authors found that the proposed model was useful for increasing profit while reducing emissions which benefits the environment. The authors of [20] recommended the implementation of a DR with ESSs in a VPP environment as a means to reduce the unpredictable behaviour or RESs and enhance the reliability of the power system. The proposed strategy attempted to optimize social wellbeing.…”
Section: Existing Literature and Research Gapmentioning
confidence: 99%
“…In Equation ( 1), S is the representation of the solar irradiance in (kW/m 2 ). What follows are the Equations used for determining the Beta PDF parameters, such as (α and β) [22][23][24][25].…”
Section: Modeling Of Solar Irradiancementioning
confidence: 99%
“…However, the uncertainty of a new power system with a high proportion of renewable energy is significantly enhanced due to the innate nature of randomness, intermittency, and volatility of wind and photovoltaic power. Compared with the traditional power grid dominated by synchronous power generation, dispatch operators are faced with much more severe challenges of real-time power balance due to the complex and changeable characteristics of system operation [2][3][4].…”
Section: Introductionmentioning
confidence: 99%